Co-occurrence of behavioural risk factors for non-communicable diseases and mortality risk in Spain: a population-based cohort study - Iñaki Galán; Cristina Ortiz; Carmen Rodriguez-Blazquez; Teresa López-Cuadrado; Ana Ayuso-Álvarez (BMJ Open)
Objectives This study aims to estimate the impact of the co-occurrence of behavioural risk factors on mortality in the Spanish adult population.Design Population-based cohort study based on data from the 2011–2012 Spanish National Health Survey and the 2014 European Health Survey (n=35 053 participants ≥15 years of age) both linked to mortality data as of December 2022. Risk factors included tobacco use, high-risk alcohol consumption, low adherence to the Mediterranean diet, leisure time sedentary lifestyle and body mass index outside the 18.5–24.9 kg/m2 range. Deaths from any cause (n=2784), from diseases of the circulatory system (n=678) and from tumours (n=869) were identified. Standardised rate differences (SRD) and standardised rate ratios (SRR) were estimated using Poisson regression models adjusted for sociodemographic variables.Results Compared with those with no unhealthy behaviours, overall mortality risk increased gradually as the co-occurrence of risk behaviours increased. Individuals with two factors had an SRD of 3.0 deaths per 1000 person-years (95% CI 1.8; 4.3) and an SRR of 1.88 (95% CI 1.35; 2.62). A coexistence of five risk factors increased SRD and SRR to 11.5 (95% CI 7.2; 15.8) and 4.34 (95% CI 2.84; 6.63), respectively. The association was stronger among individuals under 65 years of age, whereas it did not vary by sex and educational level. Those reporting five risk factors had SRRs of 6.35 (95% CI 2.91; 13.83) and 2.57 (95% CI 1.11; 5.98) for tumour-related and cardiovascular disease mortality, respectively.Conclusions The co-occurrence of unhealthy behaviours increases the risk of overall and cause-specific mortality. Targeting multiple risk behaviours should be incorporated into the public health strategy.